A weighted and cumulative point system for accurate scoring of intestinal pathology in a piglet model of necrotizing enterocolitis - Simone Margaard Offersen; Nicole Lind Henriksen; Anders Brunse (Elsevier, 2024)
Necrotizing enterocolitis (NEC) is a serious condition in premature infants, in which a portion of the intestine undergoes inflammation and necrosis. The preterm pig develops NEC spontaneously, making it a suitable model for exploring novel NEC treatments. We aimed to revise the intestinal scoring system to more accurately describe the diversity of NEC lesions in the preterm piglet model. We included 333 preterm piglets from four experiments, each delivered via cesarean section. The piglets were fed either a gently processed (GP) or harshly processed (HP) milk formula for 96 h before euthanasia. At necropsy, the gastrointestinal tract was assessed with 1) an established 6-grade score and 2) a descriptive approach focusing on the distribution and severity of hyperemia, hemorrhage, pneumatosis intestinalis (intramural gas), and necrosis. Subsequently, the descriptive registrations were converted into a weighted and cumulative point (WCP) score. Compared to the 6-grade score, the WCP score enabled a greater segregation of severity levels, especially among organs with more prominent NEC lesions. IL-1β in small intestinal lesions and both IL-8 and IL-1β in colon lesions correlated positively with the WCP scale. A histopathological grade system (0-8) was established and revealed mucosal pathology in lesion biopsies, which were not recognized macroscopically. Finally, the WCP score showed a higher NEC-promoting effect of the HP formula compared to the GP formula. The descriptive registrations and extended score range of this revised intestinal scoring system enhance the accuracy of describing NEC lesions in preterm pigs. This approach may increase the efficiency of preclinical NEC experiments.